Problematika Pembelajaran Agama Islam Di Sekolah Menengah Kejuruan Negeri 13 Malang - Subhan Adi Santoso (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract: Education is the key to the formation of competent human resources in building the nation. Education has a very urgent role to ensure the development and survival of a nation. Education is also a benchmark to advance a nation, and to mirror the personality of its people. The author will choose a location study at Vocational High School 13 Malang, the subject of his research is the principal, vice principal part of the curriculum, Islamic religious education teachers, and students. In this study the authors used three kinds of data collection techniques are methods of observation, interviews, documentation methods. Research findings have been obtained by the authors as follows: Problem in Students in Learning Islamic Education, Problem Educator (Teacher) In the Islamic Religious Education Learning, Problem Management in Islamic Religious Education Learning, Problem curriculum in Islamic Religious Education Learning, Problem Facilities and Infrastructure In Islamic Religious Education Learning,Environmental Problem In Islamic Religious Education Learning